THE RISK FACTORS OF SAFETY RIDING BEHAVIOR: A SCOPING REVIEW - Syafira Azzahra; Siti Rahmah Hidayatullah Lubis (PT. Berkah Digital Teknologi, 2025)
Purpose of the study—This study aims to determine the risk factors influencing riding safety behavior in motorcyclists. Research method—This study used the scoping review method using the PEOS framework and PRISMA flowchart in searching previous articles on six journal databases, namely PubMed, Science Direct, Garuda (Garba Reference Digital), Directory of Open Access Journal (DOAJ), JSTOR, and Taylor and Francis. Of the 3,042 identified articles, 13 were selected because they met the inclusion criteria. Result—Internal factors influencing safety riding behavior are age, risk perception, Knowledge, consumption of alcohol and drugs, attitude, and work stress. External factors influencing safe riding behavior are road conditions, riding time, type of motorbike, mileage, education provision, workload, and policies Conclusion—Efforts and strategies are needed from the government as a policy maker, such as combining law enforcement with the provision of education and training, implementing stop lines at local crossroads, and strict policies for protection for delivery couriers.